Coconut Fiber Cement Panels as Wall Insulation and Structural Diaphragm - Brose, Andrew; Kongoletos, Johnathan; Glicksman, Leon (Frontiers in Energy Research, 2019)
The study considers applications for natural fiber composites for affordable housing projects located in the two districts of Gujarat, India and Gorkha, Nepal with the goal of addressing issues of thermal comfort and lateral loading from seismic activity. To help alleviate some of these issues, the team worked with the Hunnarshala Foundation, in Bhuj, Gujarat, India, to develop a fiber cement composite that could be applied to the interior or exterior of a home and provide both insulative and structural improvements. Thermal conductivity of the composites were measured using a heat flux machine and experimental results of 0.16 W/m•K to 0.19 W/m•K showed an improvement in thermal conductivity compared to current wall cladding materials ranging from 1.60 - 1.88 W/m•K. Modeling of the building envelope was completed using the EnergyPlus™ tool and show that homes using the fiber cement composites would have an overall reduction in heating requirement of Nepalese homes by 14% and a reduction of 11% for homes in North India. The study used coconut husk fibers (referred to as coconut coir), rattan, and pine wood fibers in addition to Portland cement, fly ash, and hydrated lime in the fabrication of fiber cement composite samples. Flexural strength of these fiber samples were 70% stronger than comparison specimens, suggesting possible application for wall cladding to reduce out-of-plane failure during seismic events. Field tests conducted in Gujarat validated lab results as well qualitative perceptions of the material. Continued work with local partners presents several possible applications of coconut coir fiber cement composites for the retrofit existing housing and construction of new buildings.